Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Produk Sepatu Ventela (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2019) - Aprilia Dyah Wulandari; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of product quality, price, and promotion variables on purchasing decisions for ventela shoe products. This research uses case studies on students from the Faculty of Economics and Business, Islamic University of Malang class of 2019 who were selected by Acidental Sampling. Determination of the number of samples using the Malholtra formula and the results obtained were 100 respondents. Data collection was carried out using a questionnaire. Data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteroscedasticity test), Multiple Linear Regression Analysis, Statistical Test (t test), and Coefficient of Determination Test (Adjusted R2) and Process analysis using SPSS 21. The results of the study stated that the variables of product quality and promotion had an effect on purchasing decisions, while prices had no effect on purchasing decisions. Keywords: Product Quality, Price, Promotion, Purchase Decision